Collaboration Humans And Robots Supported By Artificial Intelligence (AI) In Serving Customers - Yuliani, Maulidina; Tambunan, Yohara G.M.; Khalijah, Putri; Situmorang, Syafrizal Helmi; Sembiring, Beby Karina Fawzeea (Jurnal Ilmu Sosial Mamangan, 2024)
This study discusses the impact of Human-Robot Collaboration (HRC) supported by Artificial Intelligence (AI) on healthcare services. customers. It is based on four types of intelligence - mechanical, analytical, intuitive and empathetic - and how these intelligences the integrated to in HRC For give service Which more efficient And personal to customer. Benefit from HRC Which supported AI highlighted, including subtraction cost operational, improvement productivity, taking decision Which more Good, And improvement experience customer. However, article This Also discuss challenge in implementing this approach, such as the potential loss of jobs due to automation, and emphasizing the importance of implementing ethical and responsible. This study has significant practical and academic implications, warning that ongoing research is needed to understand the potential and limitations of AI-enabled HRC in healthcare services customer. Overall, through a literature review, this article aims to appeal to the reader's critical spirit and explore topics on the transformative power of AI in customer service